Quality of Life and Psychosocial Impact of the Lockdown Due to the COVID-19 Pandemic on Patients with Cancer: Results of a Preliminary Analysis - Maria Ferrara; Elisa Langiano; Lavinia Falese; Antonella De Marco; Elisabetta De Vito (Medical Sciences Forum, 2022)
The aim of this study was to assess the quality of life and the psychosocial impact of the lockdown due to the COVID-19 pandemic on cancer patients in Italy using a questionnaire aiming to detect the psychosocial impact of the lockdown. Among their basic needs, psychological and medical support appeared to be prevalent followed by the need for safe transportation to reach the treatment facilities. Internet was their main source of information on the coronavirus. Although 72.7% of patients did not give up hospital therapies, 32.6% complained of variations in the continuity of the treatments. The majority of the sample (73.8%) was scared to be infected but 21.9% did not share their anxieties and worries with others. The multivariate regression analysis showed that a pessimistic perception of their quality of life was influenced by living in extra-urban areas and alone (OR 1.51), while the perception of reduced physical function resulted in a state of anxiety and stress (OR = 1.8) and difficulties in the continuity of medical assistance (OR = 1.3).